Climate Change Impact Analysis on Food Availability in the Province of Kalimantan Utara, Indonesia - Harini, Rika Harini; Susilo, Bowo; Ariani, Rina Dwi; Supriyati, Supriyati (Indonesian Journal of Geography, 2023)
Climate change directly affects crop yields as a measure of food availability by, for example, causing harvest failure. El Niño and La Niña are two weather patterns affecting the climate of Indonesia, a country at low latitudes, and reportedly increasing its vulnerability to food insecurity. This research was designed to analyze climate change impact on food availability in the Province of Kalimantan Utara using secondary data(temperature, rainfall, and agricultural production) as the base data. It employed quantitative descriptive analysis to explain the study results expressed in maps, tables, and graphs and the regression technique to determine climate change impact on food availability. The regression analysis revealed that climate change significantly shaped the availability of rice (0.008) and vegetable commodity (0.000) but posed insignificanteffects on tubers, legumes, and fruits. Apart from climate change, food availability also depends on land management, land suitability, capital, technology, and cultivated plant variety